DESAIN SISTEM INFORMASI UNTUK PENDIDIKAN ANAK-ANAK DI PLAYGROUP - Mia Fitriawati; R H Lestari (Jurnal Teknologi Informasi dan Pendidikan, 2020)
Parents are working harder due to the increase needs of necessities of life. This causes mothers to work so that they meet these necessities. As a result, mothers leave their children aged 2 (two) to 4 (four) years in the play group. However, the children development is often out of hand because it is not properly recorded. Recording children development manually has several weaknesses, one of them is damaged children development recording book. Based on this problem, this research aims to develop information systems design for early childhood education services to monitor children development. The method used was SDLC. The result of the research is information system as children development monitor in early childhood education services and tool for teachers in managing the information regarding children growth and development effectively and efficiently.